Censorship and cultural revolution: political change and ideological control in postwar socialist Romania, 1945-1953 - Chiorean, Andru (2020)
In this thesis, I aim to provide a fresh perspective on a traditional question, namely that of the thorny relationship between cultural production and political power. My subject is the Romanian communist state in the first postwar decade, a period during which it was striving to effect both political control and social change, and to a large extent looked to culture as a way of achieving these objectives. My focus is how the Romanian communist state’s apparatus of media control operated during its formative period, and how it sought to calibrate and mediate the socialist cultural agenda. Specifically, the thesis will examine the roles, structures and processes of Romanian communist institutional censorship.In most scholarship on Romanian communist history, censorship has been conceived and studied as one of the principal instruments of communist repressive power in the cultural sphere. I do not deny that that Romanian institutional-regulatory censorship, be it wielded by the censor’s office, the Central Committee’s Agitprop agency, or the secret police, played a proscriptive role. However, in this thesis I am interested more in how this censorship, when situated in and understood aspart of wider formative cultural processes enacted by the new state (that might loosely be termed ‘cultural revolution’), can also be understood as a necessary condition for the formation of the speaking socialist subject. In this way, I argue, in communist cultural production, censorship also –and perhaps more importantly–fulfilled a productive function in the project to consolidate and legitimise the power of the new state, through the creation of new social norms and values and, ultimately, of new subjectivities. In this thesis, I will be looking at the early postwar cultural construction from the perspective of the Party-state’s cultural producers and regulators. Using extensive archival materials, I will focus on three model institutions of cultural revolution: the Romanian Communist Party’s Agitprop agency, the censorial body, and the Radio Station. My aim is to analyse how a distinct socialist culture with its own system of production, regulation, distribution, and reception was institutionally established in postwar Romania, and thus demonstrate that the new state’s cultural revolution was not only a coercive and disciplinary project but a constructive one as well. To be sure, the communist state monopolized and directed the cultural sphere but, in opposition to traditional accounts, I maintain that it was not a domination based on destruction. As I shall show, the socialist culture did not emerge in a vacuum but drew on local traditions, institutional continuities and historical particularities, as much as on ideological improvisation and practical expediency. A close, empirically-based and theoretically-informed study of the evolving structures, processes and functions of censorship in this period offers us a new way of conceptualising and understanding Romanian communist state-building, political transition and social transformation.